A indefinição das fronteiras entre o público e o privado na educação básica : da liquefação progressiva da ideia de escola republicana e do conhecimento como um bem comum à necessidade de instituição dos comuns da educação - Consaltér, Evandro (2021)
In this research, I defend the thesis that there is a slow and gradual process that has been causing the indefiniteness of the boundaries between public and private on basic education and, as a consequence, the progressive liquefaction of the idea of republican school and knowledge as a common good. This process is materialized, above all, by distinct educational policies and different forms of privatization of basic education, driven by educational neoliberalism and by the desire to conceive education as a large market. In this context, the socio-historical understanding of a school guided by an ideal of a republican character, with a conception of education for all children intrinsically of equal value, opens space for a conception that prioritizes the individual performance of schools and students, for processes of differentiation and hierarchies, channeling, selection and exclusion. Thus, considering the necessity and the social relevance of preserving and strengthening the school as a republican institution, a source of knowledge as a common good and resistant to the attacks of educational neoliberalism, I have chosen the following question as a research problem: How public-private partnerships established on basic education can lead to the progressive liquefaction of the idea of the republican school and knowledge as a common good? To achieve this purpose, I develop a qualitative research, using theoretical-bibliographic and documentary studies, anchored in the deductive-analytical method. The theoretical contribution is based on Abrams (2016), Adrião (2008; 2014), Akkari (2011), Dardot & Laval (2016; 2017), Laval (2004), Masschelein & Simons (2018), Peroni (2013; 2018) and Pires (2015). From the literature review (state of knowledge), two theoretical chapters are constituted about the investigated theme, aiming to support the bibliographic and documentary analysis that constitute the following chapters. The general objective of this thesis is to characterize how Public Private Partnerships - PPPs established on basic education can lead to the progressive liquefaction of the idea of the republican school and knowledge as a common good. This broad purpose subdivides into the following specific objectives: i) to contribute to the understanding of what education is as a public good, a school in the republican perspective and the knowledge as a common good; ii) to analyze the implications of an education guided by the business perspective, that strengthens educational neoliberalism; iii) to show how the privatization of the school, especially through public-private partnerships, can cause the progressive liquefaction of the idea of republican school and knowledge as a common good; iv) to show that the institution of education commons can be an alternative to face the voracity of educational neoliberalism. As research results, we point out that the capitalist discourse consumes both natural resources and symbolic institutional forms, such as the school. Thus, facing this process of “school desymbolization”, the perpetration of the private sector in public education, in its next step, contributes to promoting the liquefaction of the school institution, not to make it disappear, but to dominate it. In this context, we indicate the Global Citizenship Education and the decolonization of the curriculum as possible paths for the institution of the commons of education and the defense of a school as a public right, equal for all, regardless of social class, color, political and religious spectrum.